Passive Range-of-Motion Exercise and Bone Mineralization in Preterm Infants: A Randomized Controlled Trial - El-Farrash, Rania A.; Abo-Seif, Ibrahim S.; El-Zohiery, Abeer K.; Hamed, Gehan M.; Abulfadl, Reham M. (American Journal of Perinatology, 2020)
Objective To assess the effect of range-of-motion exercise program on bone mineralization and somatic growth of very low birth weight (VLBW) infants.Study Design A total of 36 VLBW infants were randomized into 18 VLBW infants receiving range-of-motion exercise and 18 VLBW control infants receiving tactile stimulation for 4 weeks. Laboratory investigations were performed at baseline and postexercise and included serum calcium, serum phosphorus (s.PO4), magnesium, alkaline phosphatase (ALP), urinary calcium/phosphate ratio, and serum carboxy-terminal cross-linked telopeptide of type 1 collagen (CTX). Dual-energy X-ray absorptiometry was performed at the end of the exercise protocol to measure bone mineral content, bone mineral density (BMD), bone area, lean mass, and fat mass.Results The weight and the rate of weight gain were significantly higher (p < 0.001) in the exercise group compared with controls postexercise. Also, higher s.PO4, lower ALP, and lower urinary calcium/phosphate ratio were observed postexercise in the exercise group (p = 0.001, p = 0.005, and p = 0.04, respectively), whereas serum CTX showed no difference between the two groups (p = 0.254). Postexercise BMD significantly improved in the exercise group (p < 0.001) compared with controls.Conclusion Although the sample size was small, we may be able to suggest favorable effects of range-of-motion exercise versus tactile stimulation on bone metabolism, BMD, and short-term growth in VLBW infants.
Keywords: metabolic bone disease; physical activity; bone mineral density; preterm infant